Die mediale Feminisierung und Heterosexualisierung des Frauenfußballs im Zuge der Fußball-Weltmeisterschaft der Frauen 2011 - Schacht, R. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Due to its unexpected media attention, the Women.s World Cup 2011 represents a milestone in the media coverage of women.s football. However, this is a result of a new and aggressive marketing of the heterosexual female attractiveness and the distinct aesthetics of women.s football and female footballers. The present article analyses, how the mass media have contributed to a feminization and heterosexualization of women.s football in the public awareness by (re-)constructing traditional gender differences. The investigation takes the form of a content analysis of four supraregional weekly German newspapers.